Esej o aktualność teorii Stuarta Halla w kontekście badań nad blogosferą - Knast, Patrycja Kinga (Kultura-Społeczeństwo-Edukacja, 2018)
This essay is talking about topicality of Stuart Hall theory. Author of essay is contending that the Coding/encoding theory of Stuart Hall is still useful in works on blogosphere. In essay author explained the Coding/encoding theory and notions of blogosphere. The author is arguing that that using Coding/encoding theory in works about blogosphere. The author is pointing prospective tesis up.